PENGARUH FLEXIBLE WORKING ARRANGEMENT DANKEPUASAN KERJA TERHADAP KINERJA KARYAWANDIREKTORAT TEKNOLOGI INFORMASI DAN KOMUNIKASIKANTOR PUSAT DITJEN PAJAK - Yulfika Anindya Farha, - (2021)
This research is using quantitative study aimed to see wheter if there is effect of flexible working arrangement and job satisfaction on the job performance or not. A structured questionaire was used as an instrument for data collection, with IT staff in the Directorate of Information and Communication Technology, Head office Directorate General of Taxes By using Slovin wit the method of Non-Probability Sampling with the type of purposive sampling and 75 sample units. Data collection is used through distributing questionnaires. The data analysis technique used is themethod Partial Least Square (PLS). The results of this study indicate that flexible working arrangement have a positive effect on job performance and also job satisfaction have a positive effect on job performance